Management of iatrogenic colorectal perforation: From surgery to endoscopy - Cai, Shi-Lun (World J Gastrointest Endosc, 2015)
Iatrogenic colon perforation is one the most pernicious complications for patients undergoing endoscopic screening or therapy. It is a serious but rare complication of colonoscopy. However, with the expansion of the indications for endoscopic therapies for gastrointestinal diseases, the frequency of colorectal perforation has increased. The management of iatrogenic colorectal perforation is still a challenge for many endoscopists. The methods for treating this complication vary, including conservative treatment, surgical treatment, laparoscopy and endoscopy. In this review, we highlight the etiology, recognition and treatment of colorectal iatrogenic perforation. Specifically, we shed light on the endoscopic management of this rare complication.